Pengujian Eksperimental Perbandingan Konsumsi Bahan Bakar dan Emisi Gas Buang Dengan Beberapa Jenis Bahan Bakar Pada Sepeda Motor - Firsan, Muhammad; Mangalla, Lukas Kano; Hasanudin, La (Teknik Mesin Universitas Halu Oleo, 2022)
Air pollution is caused by the activities of motorized vehicles that emit exhaust gas emissions, including CO, CO2, HC, NOX, SOX, and particulates. The purpose of this study was to determine how the effect of fuel variations on the time of fuel consumption and exhaust emissions on motorcycles and to find out how the composition of mixing premium fuel with ethanol affects the time of fuel consumption and exhaust emissions. This study uses 4 types of fuel, namely premium, pertalite, E-5, and E-10 and tested using 3 variations of throttle openings. From the test results, it is found that the most fuel consumption is found in the wide throttle opening on premium fuel = 0.77 L/h. For the results of the lowest CO and HC exhaust emissions found in the wide throttle opening on the E-10 fuel where the emission value of CO = 1.98% and HC = 1425 ppm. So it can be concluded that in comparison with the time of fuel consumption, the higher the throttle opening, the faster the fuel consumption will be and for exhaust gas emissions, the higher the throttle opening, the lower the CO and HC emission values. Mixing premium fuel with ethanol can make the fuel consumption time slower than pure premium and can also reduce the content of CO and HC exhaust emissions.Key words: Fuel, Exhaust emissions, Fuel consumption